Analyzing Adoption Impediments in Soil Health Card based Fertilizer Application by Farmers - Sarvesh Kumar (Indian Journal of Extension Education, 2025)
The study was completed in Harda district of Madhya Pradesh. Present study was completed in the year 2023. The average data of continuous SHC based study and extension based responses were collected through developed interview schedule, random group discussion, meetings and personal interviews and data was analyzed to find out the adoption extent, impediments, regarding of soil health card based recommendations among farmers of different villages provided or benefited under different schemes of state departments and Krishi Vigyan Kendra and line departments. The importance of soil health card based fertilizers use was told to farmers before the response collection in the initiation of crop season through training and other awareness programmers. The impediments were recorded to know the status of adoption of soil health card based fertilizers application among farming community in Soybean and Wheat major crops. The continuous motivation of educated farmers having good social participation and mass media exposure by KVK scientists through conducting SHC based trials and demonstrations, backstopping by field extension activities and success story sharing have significant role in enhancing the adoption rate and balance use of fertilizers dozes for improving farmers income and cost saving in Harda district of Madhya Pradesh.